Acaricidal effect of the antimicrobial metabolite xenocoumacin 1 on spider mite control - Jiaxing Wei; Hong Yan; Jie Ren; Guangyue Li; Bo Zhang; Xuenong Xu (Journal of Integrative Agriculture, 2024)
The two-spotted spider mite, Tetranychus urticae Koch, is one of the most harmful pests in many agroecosystems worldwide. To effectively manage this pest, there is an urgent need to develop novel bio-active acaricides that support integrated pest management strategies targeting T. urticae. In this study, we explored the acaricidal effects of xenocoumacin 1 (Xcn1) on T. urticae and its predator Neoseiulus californicus using the highly purified compound. Xcn1 was extracted and purified from the cell-free supernatant of the Xenorhabdus nematophila CB6 mutant constructed by the easy promoter activated compound identification (easyPACId) method. When the concentration of Xcn1 exceeded 100 μg mL−1, the survival rate of spider mite adults declined to below 40% and the fecundity was decreased by 80% at six days post-application. At concentrations of 25 and 50 μg mL−1, Xcn1 significantly impeded spider mite development by inhibiting the molt. However, neither concentration had any adverse effects on the survival or reproduction of the predatory mite N. californicus. The results from laboratory and semi-field experiments consistently demonstrated the effectiveness of the antimicrobial metabolite Xcn1 in controlling pest mites at both the molecular and physiological levels. Our study offers a promising possibility that combines the compatible biocontrol agents of Xcn1 and predatory mites for integrated pest mite control.